Lost decades : the making of America's debt crisis and the long recovery - Chinn, Menzie David (W.W. Norton & Co., 2011)
Examines the role federal borrowing played in the economic collapse of 2008, describing the economic and political causes of the collapse, and discussing what the continuing impact of the debt and foreign borrowing will be on the United States in the twenty-first century.